Coriander Seed Extract ( Coriandum Sativum L ) as an antioxidant - Irza Haicha Pratama; Ermi Girsang; Tan Suyono (CV. Inara, 2022)
Diabetes mellitus (DM) is a disease characterized by hyperglycemia, lipoprotein abnormalities, increased basal metabolic rate, enzyme deficiency, and high oxidative stress. This research is an experimental study that aims to explore coriander seed extract (Coriandrum sativum L) using Post-Test Only Control Group Design. This study to was conducted to see the antioxidant potential (DPPH, ABTS, LC-MS/MS) of coriander seed extract (Coriandrum sativum L). Based on the test results, coriander seed extract contains very high phytochemicals, one of which is alkaloid compounds, and in vitro test results found DPPH antioxidant with an average IC50 value of 14.33 g/mL and at the lowest concentration (6.25 g/mL). g/mL), CSE also showed the highest antioxidant activity against ABTS trapping with an average IC50 value of 74.07 g/mL and the results of LC-MS/MS obtained samples of coriander extract containing 0.00009% chlorogenic acid and quercetin compounds. of 0.00012%.